Introduction to classical mechanics with problems and solutions - Morin, David; Morin, David (New Delhi, Cambridge University Press, 2007)
This textbook covers all the standard introductory topics in classical mechanics, including Newton's laws, oscillations, energy, momentum, angular momentum, planetary motion, and special relativity.
Appendix A-J 675-712p.; References 713-715p.; Index 716-719p.; Reprint 2018.
Keywords: Central forces; General relativity; Oscillations; Relativity; Physics